2011
DOI: 10.1111/j.1442-2042.2011.02918.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation of synchronous bilateral renal cell carcinoma

Abstract: Objectives: The treatment of synchronous bilateral renal cell carcinoma is challenging. Radiofrequency ablation has been increasingly applied in the management of renal tumors. Herein, we report our experience of radiofrequency ablation on 12 patients with synchronous bilateral renal cell carcinoma. Methods: From March 2006 to September 2010, 12 patients with bilateral synchronous sporadic renal cell carcinoma (29 lesions overall) were identified from our kidney database. The mean age was 62.3 years (range 35-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…Overall, there are limited data on patients undergoing synchronous bilateral PN. In addition, only one previous study has reported on the use of renal mass ablation for the treatment of bilateral renal masses . As such, the present study provides novel data on outcomes of patients with such bilateral renal tumours.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Overall, there are limited data on patients undergoing synchronous bilateral PN. In addition, only one previous study has reported on the use of renal mass ablation for the treatment of bilateral renal masses . As such, the present study provides novel data on outcomes of patients with such bilateral renal tumours.…”
Section: Discussionmentioning
confidence: 85%
“…If technically feasible, bilateral partial nephrectomies (PNs) are often the preferred strategy because of the benefits of renal functional preservation when compared with radical nephrectomy. More recently, renal mass ablation has emerged as a treatment alternative for patients with renal masses , but there are limited data on the extension of ablative techniques to the treatment of bilateral renal masses .…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the area of WI, unblocking and segmental renal artery clamping technique was applied. Although the operation demand high equipment quality and operation technique, more and more departments carrying out these techniques in recent years [ 10 12 ]. What’s more, our previous study has been demonstrated that patients underwent segmental artery clamping have better early recovery comparing by 3-month postoperative GFR levels [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lowrance et al ( 2 ) hypothesized that patients with bilateral RCC have more severe preoperative renal dysfunction than those with unilateral RCC. Balancing preservation of renal function and oncological efficacy is a challenge for urologists managing individuals with bilateral RCC ( 6 ).…”
Section: Introductionmentioning
confidence: 99%